2017
DOI: 10.1007/s10888-017-9352-z
|View full text |Cite
|
Sign up to set email alerts
|

Intertemporal deprivation in rural china: income and nutrition

Abstract: We analyse intertemporal poverty in two important dimensions -income and nutrition -in less developed northwest China during 2000-2004. Household intertemporal deprivations in these dimensions are estimated using measures which are sensitive to the precise sequence in which poor and non-poor spells occur. A generalised recursive selection model is then proposed to investigate the determinants of intertemporal deprivation in each dimension, allowing for the possibility that correlated unobservables drive the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…This observation was also confirmed by other studies (e.g., [62]), which asserted that providing CAP instruments for agriculture had a decisive influence on the increase in income in EU-12 countries and on a decrease in the disparities between the income of farmers and remuneration obtained in other occupations. Hence, agricultural policy is of key importance for reducing agricultural deprivation [63][64][65][66]. When it comes to the eco-efficiency thread, Grovermann et al [67] argued that innovative systems enabled by institutional help connected with production in agriculture increase overall efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…This observation was also confirmed by other studies (e.g., [62]), which asserted that providing CAP instruments for agriculture had a decisive influence on the increase in income in EU-12 countries and on a decrease in the disparities between the income of farmers and remuneration obtained in other occupations. Hence, agricultural policy is of key importance for reducing agricultural deprivation [63][64][65][66]. When it comes to the eco-efficiency thread, Grovermann et al [67] argued that innovative systems enabled by institutional help connected with production in agriculture increase overall efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In poverty-stricken areas, inadequate diets are a common problem. Inadequate diets and undernutrition uniformly affect asset accumulation and labor productivity in most states (Dutta, 2015; You et al , 2018), significantly limiting countries' development (Jha et al , 2009). Moreover, more than half of the UN's sustainable development goals are related to food security and nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Agriculture is characterized by seasonality, the scale of risk and uncertainty resulting from weather conditions, variable work intensity and cyclicality of production which have destabilizing effects both on agricultural income and profitability of agricultural production [36,38]. This is also confirmed by the results of studies of other authors in which, on the example of various groups, it was shown that agricultural policy is of key importance for reducing agricultural deprivation [39][40][41][42]. Thanks to the CAP, this is also reflected in the EU, which is confirmed by the results of our analyzes.…”
Section: Agricultural Income Against the Non-agricultural Incomementioning
confidence: 86%